Kondisi Kehidupan Masyarakat di Tanah Batak Setelah Masuknya Belanda - Handa Khapoor Tamba; Hotmadian Delima Haloho; Arfan Diansyah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This research was conducted with the aim of knowing how the living conditions of the people, especially on the island of Samosir, after the arrival of the colonists to the Batak land. The research method used in this research is using historical methods, namely heuristics or source collection, verification or source criticism, interpretation or interpretation and historiography. Therefore, the data was collected through books and journals that discussed the living conditions of the people, especially on the island of Samosir after the arrival of the colonists to the Batak lands as well as documents in the form of pictures taken from the KITLV magazine. So, the results found from this study are, after the arrival of the colony, namely the Dutch to the Batak land specifically on the island of Samosir, the condition of the community at that time was growing, characterized by more and more types of livelihoods, people's lives also increased, beliefs or spirituality experienced changes, maronan activities (shopping/buying and selling transactions) as economic, social and so on. So, it can be concluded that the arrival of Europeans, especially the Netherlands, had a profound impact on people's lives.